Qualitative Comparative Analysis (QCA) in Spatial Planning Research and Related Disciplines: A Systematic Literature Review of Applications. (August 2019) - Verweij, Stefan; Trell, Elen-Maarja
Qualitative comparative analysis (QCA) is a potentially interesting method for spatial planning researchers. Although increasingly used, its application in spatial planning research is lagging behind other disciplines. We conducted a systematic literature review of QCA applications in spatial planning and related disciplines (SPARD), addressing two questions: when, where, and how is QCA used in SPARD and what are the main advantages of QCA for spatial planning research? We found that the main reasons why QCA is used in SPARD are its sensitivity to context, its ability to use small-/medium- n cases, and its attention to causal complexity.